CP-019 Hospital pharmacists' interventions in a central hospital. (24th February 2014) - Parrinha, A; Lobo Alves, M; Branco, R; Goulão, I; Fernandes, C; Lopes, C; Madureira, B; Cavaco, P; Santos, S; Carreira, S; Viegas, E; Falcão, F
Abstract : Background: Several studies have demonstrated the positive impact of clinical pharmacy services in the hospital setting. Interventions by clinical pharmacists have been shown to reduce the frequency of drug-related problems. Pharmacist interventions (PIs) are defined as a professional activity performed by pharmacists, directed towards improving the quality use of medicines and resulting in a recommendation for a change in the patient's drug treatment. Purpose: To characterise all PIs recorded in the electronic medical record and quantify their acceptance by the medical team. Materials and methods: An observational, retrospective study was carried out in a 350-bed central hospital, between January and June 2013. All the PIs recorded in the electronic medical record during the study period were eligible for inclusion; verbal PIs and related to clinical pharmacokinetics were excluded. Results: 1449 PIs were performed during the study period. The majority of these PIs involved the following therapeutic classes: antibacterial (25%), CNS (24%), cardiovascular (18%) and blood (9%). 147 drugs were targeted in an intervention; acetaminophen (18%) was the subject of the largest number of pharmacist interventions, followed by enoxaparin (13%) and amoxicillin/clavulanic acid (10%). When we looked at the type of intervention we found that most corresponded to dose adjustment for renal failure (29%), change of administration route (24%) or other dose adjustment (9%). Discharge, transfer between clinical services and drug discontinuation led to it only being possible to assess 69% of interventions performed. The acceptance rate was 48%. Conclusions: Our results, in particular those referring to dose-dependent problems, confirm the need for pharmacotherapy follow-up. From this study it can be concluded that a high percentage of PIs are focused on a limited number of drugs, suggesting the need to make specific recommendations in order to improve drug use. The ultimate goal of PI is to improve health outcomes for each patient by promoting the rational use of medicines. No conflict of interest.